2018
DOI: 10.1002/jso.25013
|View full text |Cite
|
Sign up to set email alerts
|

Nasolabial propeller perforator flap: Anatomical study and case series

Abstract: Although nasal alar reconstruction continues to be a challenging plastic surgery procedure, the nasolabial propeller perforator flap is an excellent choice for such because it allows a precise skin island design, is less bulky, has a wide arc of rotation, and facilitates one-staged reconstruction without increasing the rate of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Previous studies have reported that the facial arterial perforator flap provides satisfactory results for repair of alar defects (8,9). However, the flap pedicle used in this procedure required tissue removal and additional treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that the facial arterial perforator flap provides satisfactory results for repair of alar defects (8,9). However, the flap pedicle used in this procedure required tissue removal and additional treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, other regions of the skin adjacent to the nose, such as the skin from the nasolabial groove and cheek, are frequently used to create flaps (6) and are particularly favorable for defects affecting more than 50% of the nasal aesthetic subunits (7). Among the flap procedures, the facial artery perforator flap method is good for repairing defects of the alar subunit (8)(9)(10). This study aimed to describe the use of the sequential facial artery perforator flap created from nasolabial fold tissues to reconstruct neoplastic nasal alar subunit defects with the achievement of an appropriate cosmetic result.…”
Section: Introductionmentioning
confidence: 99%
“…Similar propeller flap articles describe reconstruction of difficult medial canthal defects, alar defects, and lateral nasal defects using various propeller flaps based on supratrochlear arteries, facial artery perforators, and central arteries. [3][4][5][6][7] The common unifying theme of all these reconstruction options is that they provide definitive coverage in one stage rather than multiple stages. 8 I applaud the authors for adding to the literature in a topic that has been one of the oldest and best-studied topics in Plastic Surgery.…”
mentioning
confidence: 99%
“…It uses tissue from under the chin and neck to resurface the entire nasal defect. Similar propeller flap articles describe reconstruction of difficult medial canthal defects, alar defects, and lateral nasal defects using various propeller flaps based on supratrochlear arteries, facial artery perforators, and central arteries 3–7 . The common unifying theme of all these reconstruction options is that they provide definitive coverage in one stage rather than multiple stages 8 …”
mentioning
confidence: 99%
“…1,2 There are plenty of materials about external scalp defect reconstruction in the literature. [3][4][5] However, through-and-through defect reconstruction results are little described.…”
mentioning
confidence: 99%